VALIDITAS PENGEMBANGAN E-LKPD UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS PESERTA DIDIK DI SMA/MA - Nurul Fajriyah; Khairunnisa; Ita (Program Studi Tadris Ilmu Pengetahuan Alam, Fakultas Tarbiyah dan Ilmu Keguruan (FTIK), Institut Agama Islam Negeri (IAIN) Palu, 2022)
Education in the era of the industrial revolution 5.0 students are required to have critical thinking skills and also able to use innovative technologies for provisions in the world of lectures and the world of work. E-LKPD is an innovatively developed teaching material so that learners can improve their critical thinking skills using electronic media. The purpose of this study is to formulate the validity of E-LKPD as teaching material in improving students' critical thinking skills. This research uses the Type of Educational Development Research (EDR) research with the Tessmer formative evaluation design method which is limited by several stages, namely self-evaluation and expert review. Research data were obtained from validity instruments. The results of the study obtained the validity of E-LKPD has an average score of 3.60 with a very valid category. These results prove that E-LKPD is used to improve students' critical thinking skills.